MEDIA PEMBELAJARAN “ KAHOOT ” BBERBASIS APLIKASI GAME UNTUK PEMBELAJARAN - Isrowiyah, Isrowiyah (Cahaya Ilmu Bangsa Institute, 2025)
Kahoot is an innovative platform that has revolutionized learning methods in the digital era by presenting a game-based learning concept. Introduced in 2012, Kahoot allows educators to create interactive quizzes that can be accessed by students using devices such as smartphones or computers. With an attractive and easy-to-use interface, Kahoot encourages collaboration and increases student participation in the learning process. Research shows that using Kahoot not only increases learning motivation, but also creates a more dynamic classroom atmosphere, so that students are more actively involved in learning activities. Additionally, Kahoot serves as an effective evaluation tool, allowing teachers to conduct formative assessments directly. Features such as quiz data collection and instant feedback provide teachers with valuable information about student understanding. During the COVID-19 pandemic, Kahoot became a practical distance learning solution, helping students stay connected and motivated even though they were not learning face-to-face. With its easy access and interactive nature, Kahoot has the potential to become one of the main learning tools in the Industrial Revolution 4.0 era, supporting the development of students' digital skills for the future.